Development and characterisation of new techniques in design and build of polymeric drug delivery devices using selective laser sintering - Low, Kah Hock. (2008)
The objective of this research is to use selective laser sintering to develop a drug delivery device that can release drug in a designed manner, ideally zero-order release.